Older Adults' Relocation Transitions: Relation of Place, Leisure and Identity. Issue 2 (3rd April 2023) - Prentice, K.; Hand, C.; Misener, L.; Hopkins, J.
ABSTRACT: Research and theory suggest that leisure, sense of home, and identity are all implicated in older adults moving to new residences. An integrative review was conducted to provide a more in-depth understanding of how these concepts inter-relate and shape older adults' moving to new homes. Seventeen studies were included, and thematic analysis showed that older adults continued, adapted, and changed their leisure activities and used leisure to develop a sense of home and maintain identity. This review can inform practice and policy initiatives, and further research could enhance understanding of leisure's role in older adults' transition to new homes.